Estimación de la Huella de Carbono en Cultivos Arroceros del Distrito de Riego ASOZULIA, Norte de Santander, Mediante la Aplicación del Análisis de Ciclo de Vida - Johneder Melgarejo Castañeda; Francisco Raúl Arencibia Pardo; Belisario Peña Rodríguez (Mundo Fesc)
This study seeks to estimate the carbon footprint of rice fields in the Asozulia irrigation district, Norte de Santander, Colombia, through descriptive research that uses the Life Cycle Analysis established in the international standards ISO 14040 and ISO 14044 as a methodological reference. First, the production system is divided into three segments (study blocks) to collect primary information on the mass and energy balances involved. Subsequently, an inventory of CO2 emissions is constructed using the Ecoinvent 3.1 database. The inventory data is processed through the LCA-Manager software to quantify the impact on said footprint, which is generated in each of the study blocks. Among the results, it was found that for each hectare of cultivation, the system emits 7,316 kg of CO2 eq, and the factors with the greatest impact, in order, are irrigation, urea, fertilizers, burning of plant material, fuels, agrochemicals, seeds, agricultural machinery, and lubricants. Finally, the following strategies are proposed as alternatives to reduce the carbon footprint: application of precision agriculture technologies, laser-assisted leveling for zero slopes, modernization of the agricultural machinery fleet, mechanized transplanting techniques, favorable agronomic practices for soil recovery, elimination of burning, preventive and predictive maintenance plans, and a training plan for personnel.